Preparation and Performance Optimization of Organosilicon Slag Exothermic Insulating Riser - Jijun Lu; Jiangbing Qian; Lei Yang; Huafang Wang (Archives of Foundry Engineering, 2023)
The exothermic insulating riser played an important role in the solidification process of metal liquid for the improvement of casting quality. This paper focused on the use of organosilicon slag to replace part of the aluminum powder as an exothermic agent for the riser, to reduce production costs and turn waste into treasure. The experiments firstly studied the effect of organosilicon slag content on the combustion temperature and holding time and determined the components of the riser exothermic agent and organosilicon slag. On this basis, the effects of the content of Na3AlF6 flux and alkali phenolic resin binder on the combustion heating time and strength properties of the riser were studied. And the ratio of mixed oxidants was determined by single-factor orthogonal experiments to optimize the addition of three oxidants, Fe3O4, MnO2, and KNO3. Finally, the performance of the riser prepared after optimization was compared with that of the riser prepared with general aluminum powder. The results showed that with the mixture of 21% organosilicon slag and 14% aluminum powder as the exothermic agent, the highest combustion temperature of the prepared exothermic insulating riser was 1451℃ and the holding time was 193 s; the optimal content of Na3AlF6 flux was 4%, and the best addition alkali phenolic resin binder was 12%; the optimized mixing ratio of three oxidants was 12% for Fe3O4, 6% for MnO2, and 6% for KNO3. Under the optimized ratio, the maximum combustion temperature of the homemade riser was 52℃ and the heat preservation time was 14% longer compared with the conventional exothermic insulating riser with 25-35% aluminum powder.